Visual culture and politics in the Baltic sea region, 1100-1250 - Markus, Kersti, 1962-; Varik, Aet (Leiden : Brill, 2020)
Focusing on visual sources and the cultural landscape, Kersti Markus offers a fresh perspective on the Baltic crusades in Visual Culture and Politics in the Baltic Sea Region, 1100-1250 . The book examines how visual propaganda was used by the Danish rulers as an instrument in establishing supremacy in the Baltic Sea region. In recent decades, Danish historians have highlighted the central role of the Valdemar dynasty and the bishops supporting them in the Baltic crusades, but visual sources show how the entire society was mentally prepared for a journey with redemption waiting at the end. A New Jerusalem was being built in Scandinavia, and the crusade to Livonia was conducted under the banner of Christ.
1, Visual Sources and the Danish Crusades -- 2, Visual Rhetoric in Denmark in the Period of the Baltic Crusades -- 3, Visual Performances of Power in Sweden -- 4, From Trade to Crusade: Visby -- 5, Manifesting a Presence in Livonia and Estonia
Elektronická reprodukce.
Keywords: 12.-13. století; křížové výpravy -- Baltské moře (oblast) -- 12.-13. století; umění a politika -- Baltské moře (oblast) -- 12.-13. století; církevní architektura -- politické aspekty -- 12.-13. století; kostely -- Baltské moře (oblast) -- 12.-13. století; crusades -- Baltic Sea Region -- 12th-13th centuries; art and politics -- Baltic Sea Region -- 12th-13th centuries; church architecture -- political aspects -- 12th-13th centuries; churches -- Baltic Sea Region -- 12th-13th centuries; Baltské moře (oblast) -- dějiny -- 12.-13. století; Baltic Sea Region -- history -- 12th-13th centuries; e-knihy online; monografie; e-books online; monographs